REVIEW OF MODERN STRATEGIES UTILIZING PHARMACOLOGICAL INNOVATIONS IN PREVENTION OF DIABETIC COMPLICATIONS RELATED TO THE VISUAL SYSTEM - Juraeva S.T., (International Multidisciplinary Journal for Research & Development, 2024)
Today, diabetes mellitus (DM) is one of the priority medical and social problems, which is due to its epidemic prevalence and high disability of patients. Visual impairment is one of the disabling manifestations of diabetes. Thus, currently the leading cause of blindness among the working-age population has become diabetic retinopathy (DR), a late nonspecific vascular complication of diabetes.